A novel enzyme-linked immunostaining technique based on silk membrane for the prenatal detection of fetomaternal haemorrhage - Xinyang Li; Miyang Li; Shengbao Duan; Hongmei Wang; Yong Li; Tiemei Liu (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Developing a simple, rapid, reliable, sensitive, and cost-effective method for prenatal detection of fetomaternal haemorrhage by combining multi-aperture silk membrane with enzyme-linked immunosorbent assay (ELISA), which does not require any complicated instruments and can be visually colored, so as to provide a new method for clinical detection of fetomaternal haemorrhage.Methods: As a carrier, a chemically treated silk membrane was used to immobilize anti-A/anti-B antibody reagent. PBS washed slowly after vertically dropping red blood cells. After adding biotin-labeled anti-A/anti-B antibody reagent, PBS is slowly washed, enzyme-labeled avidin is added, and TMB is used for color development after washing.Results: When there were both anti-A and anti-B fetal erythrocytes in pregnant women’s peripheral blood, the final color was dark brown. When there are no anti-A and anti-B fetal red blood cells in pregnant women’s peripheral blood, the final color development results do not change, which corresponds to the color of chemically treated silk membrane.Conclusion: The new enzyme-linked immunosorbent assay (ELISA) based on a silk membrane can distinguish fetal red blood cells from maternal red blood cells prenatally and can be used for prenatal detection of fetomaternal haemorrhage.